Isolated fallopian tube torsion: A challenge for the timely diagnosis and treatment - Jokić Radoica (Srpski Arhiv za Celokupno Lekarstvo, 2015)
Introduction. Isolated torsion of the fallopian tube is a rare cause of acute lower abdominal pain and infrequent indication for surgical treatment. Case Outline. A 16-year-old girl was referred to the hospital due to the non-specific symptoms over period of a few months and pain acutization in the right infraumbilical region lasting for two days. Complete laboratory analyses were normal. Ultrasound examination revealed a round mass (23Ч14 mm) within the right fallopian tube with color Doppler whirlpool sign, normal ovary, and a simple ipsilateral paratubal cyst (50x40 mm). Laparoscopy showed a dilated and two times torquated right fallopian tube, as well as signs of chronic appendicitis. The tube was twisted about its longitudinal axis and it was livid, but not gangrenous. After appendectomy, fallopian tube was detorquated, cyst extracted and preservation of the tube was performed. Postoperatively, antibiotic therapy was administered based on antibiogram. On follow-up examinations within the next four months postoperative course was uneventful. Conclusion. Since there are no pathognomonic symptoms, clinical or laboratory findings, diagnosis of this condition is challenging. Familiarity with Doppler whirlpool sign can enable a timely diagnosis and treatment of isolated fallopian tube torsions. However, the diagnosis is rarely made before operation. Unlike in our case, surgery is often performed too late, and delay of intervention may result in failure to save the fallopian tube.